2012
DOI: 10.1002/mc.21899
|View full text |Cite
|
Sign up to set email alerts
|

miR‐106a is frequently upregulated in gastric cancer and inhibits the extrinsic apoptotic pathway by targeting FAS

Abstract: Emerging evidence has shown the association of aberrantly expressed miR-106a with cancer development, however, little is known about its potential role in gastric carcinogenesis. In our present study, obviously overexpressed miR-106a was found in gastric cancer tissues compared with their nontumor counterparts. Suppression of miR-106a significantly inhibited gastric cancer cell proliferation and triggered apoptosis. Bioinformatic analysis combining with validation experiments identified FAS as a direct target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 49 publications
5
49
1
Order By: Relevance
“…These data strongly support our present data in regards to CC. Moreover, miR-106a was frequently upregulated in gastric cancer and inhibited the extrinsic apoptotic pathway by targeting FAS (13). In addition, miR-106a targeted autophagy and enhanced sensitivity of lung cancer cells to Src inhibitors (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data strongly support our present data in regards to CC. Moreover, miR-106a was frequently upregulated in gastric cancer and inhibited the extrinsic apoptotic pathway by targeting FAS (13). In addition, miR-106a targeted autophagy and enhanced sensitivity of lung cancer cells to Src inhibitors (29).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have confirmed that aberrant expression of miRNAs is involved in various types of cancer, including CC, and participate in diverse biological processes such as cell growth, invasion, differentiation and metastasis (8)(9)(10)(11)(12). Recently, miR-106a, which is derived from the precursor miR-106a-363 on chromosome Xq26.2, was revealed to play a critical role in the progression of cancers (13)(14)(15)(16)(17). A previous study revealed that miR-106a functions as a regulator of cell invasion, proliferation and drug sensitivity (18).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we identified the deregulation of miR-106a in ovarian cancer. miR-106a is widely expressed in diverse human tumors, including gastric, non-small cell lung, pancreatic, colorectal and ovarian cancer (6,8,9,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Previous studies showed that miR-106a acts as a tumor suppressor or an oncogene in different cancers, depending on the different cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that miR-106a acts as a tumor suppressor or an oncogene in different cancers, depending on the different cellular context. In gastric cancer, expression of miR-106a was increased, and downregulation of the expression of miR-106a inhibited gastric cancer cell proliferation and caused apoptosis by targeting FAS (52). In non-small cell lung cancers, miR-106a inhibited the growth and metastasis of NSCLC cells by decreasing phosphatase and tensin homolog (PTEN) expression (9).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [10] have found that miR-106a is among the most highly expressed miRNAs in human gastric cancer cell lines and in primary gastric tumors. It also has been reported that the upregulation of miR-106a promotes survival of esophageal adenocarcinoma cells and confers resistance to DDP [11].…”
Section: Introductionmentioning
confidence: 99%